A Response to Welch’s Review of "Urihi A: A Terra‐Floresta Yanomami" - van der Voort, Hein (Ethnobiology Letters, 2010)
A Response to Welch’s Review of Urihi A: A Terra‐Floresta Yanomami. Bruce Albert and William Milliken with Gale Goodwin Gomez. São Paulo: Instituto Socioambiental, 2009. 207 pp., illustrations, tables, bibliography, appendices, index. Paperback ISBN: 978‐85‐85994‐72‐3.